Synthesis, Process, Morphology and Thermal Stability of N,N’-Bis(benzoyl) Tridecanedioic Acid Dihydrazide - Cai, Yan-Hua (Asian Journal of Chemistry, 2011)
Novel N,N'-bis(benzoyl) tridecanedioic acid dihydrazide was synthesized from benzoyl hydrazine and tridecanedioyl dichloride which was deprived from tridecanedioic acid via acylation and the structure of this novel bisamide compound had been characterized by FT-IR, 1H NMR. The influence of the reaction ratio, reaction time and reaction temperature to the yield of product was further investigated, molar ratio of benzoyl hydrazine: tridecanedioyl dichloride 2:1, reaction time 6 h, reaction temperature 80 ºC, the yield was 90.1 %. Scanning electron microscopy (SEM) showed the N,N'-bis(benzoyl) tridecanedioic acid dihydrazide was layered and the average size of the layered particles was 5 μm. The thermal stability of N,N'-bis(benzoyl) tridecanedioic acid dihydrazide was investigated by TGA thermal analyzer. The result showed good thermal stability of N,N'-bis(benzoyl) tridecanedioic acid dihydrazide under 165 ºC and that the decomposition of N,N'-bis(benzoyl) tridecanedioic acid dihydrazide could reach 96.9 % at 500 ºC.